Anticorruption Initiatives : Reaffirming Commitment to a Development Priority - World Bank Group (World Bank, Washington, DC, 2020)
Corruption continues to have a disproportionate impact on the poor and most vulnerable, increasing the cost of, and reducing access to, health, education, justice, electricity and other basic services, thereby exacerbating inequality. It reduces private investment as it increases risks for investors, with consequent effects on growth and jobs. It distorts public spending decisions and weakens the quality of public investments as substandard infrastructure gets built and the regulatory systems for quality control and safety are bypassed. It erodes public trust in governments, undermining their legitimacy and posing a threat to peace and stability. This paper draws on these lessons and proposes a new approach, both in terms of what we work on and how we work, focusing on initiatives to be led by the Bank’s EFI vice presidency to reaffirm the Bank’s commitment to anticorruption. The initiatives refresh approaches that are showing results, scale up those that are emerging and show promise, or experiment and innovate where fresh thinking is needed in our support to client countries to help them control corruption. In this note, corruption is seen as both a symptom of underlying governance challenges and a problem in and of itself. For practical purposes, and to keep the focus on corruption, the initiatives do not expound on the many aspects of governance that influence corruption. The paper also does not focus on efforts to control corruption risk in World Bank operations, but rather focus on the support that the EFI Vice Presidency will provide to countries in their efforts to control corruption.